Distributed DSTATCOMs for distribution line enhancement - Perera, L.; Ledwich, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
Distribution feeder voltage reinforcement by multiple site reactive power compensation systems has recently been reported by many researchers. However, voltage control by multiple DSTATCOMs across a distribution feeder may introduce control interactions and/or voltage instability. This paper addresses these control interaction issues and proposes a control scheme that alleviates interactions among controllers. The proposed control scheme also enhances proper sharing of reactive power among DSTATCOMs. A mathematical model of a distribution system with any number of DSTATCOMs is developed to investigate the performance of the control system. This mathematical model is used to conduct eigenvalue analysis to develop the criterion for controller design. The proposed control scheme is tested in time domain on a sample radial distribution feeder installed with multiple DSTATCOMs and test results are presented.